Relationship between Ig-E Levels and Lung Function Tests in Children with Asthma - Begum, JA; Islam, MI; Hoque, SKA; Islam, MT; Hossain, MZ; Matin, A (Journal of Dhaka Medical College, 2010)
Background: Asthma is the most common chronic disorder in childhood. A high level of Ig E is associated with asthma. Objectives: The present study was carried out to observe the relation of serum IgE level with lung function parameters in asthma children and apparently healthy normal children. Methods: This study was carried out in the out patient department of paediatrics, Dhaka Medical College, Dhaka between January 2010 and June 2010. Total sixty children with age range from six to fifteen years of both sexes were included in this study. Thirty children suffering from asthma and thirty apparently healthy children with no systemic disorder were taken as study population. Serum Ig-E levels were measured in all subjects using a standard Immulite assay by ELISA method. Subjects were classified as having high IgE if their total IgE level was greater than or equal to 100 IU /ml .Subjects were classified as having low IgE if their total IgE level was less than 100 IU /ml. Spirometry was conducted on all patients by using Spirolab a new generation spirometer according to American Thoracic Society standards. Data were analyzed by unpaired t test and Chi-squares test. Results: The mean percentage of predicted values of FEV1, FVC, FEV1/FVC% were significantly lower in high Ig E (>100 IU/ml) level group in comparison with low Ig E(<100 IU/ml) group. Conclusion: Therefore the result of the present study reveals that higher IgE is related with lower lung function and also there were more chance in symptoms based asthma in our study populations. DOI: 10.3329/jdmc.v19i1.6242 J Dhaka Med Coll. 2010; 19(1) : 3-6.